Advances in databases and information systems : 19th East European Conference, ADBIS 2015, Poitiers, France, September 8-11, 2015, Proceedings /: 19th East European Conference, ADBIS 2015, Poitiers, France, September 8-11, 2015, Proceedings. (2015) - Unknown
No abstract available